Preparation method of CoCrNi medium-entropy alloy and Q235B steel explosive welding composite board

By using high-strength explosives for explosive welding during the composite process of CoCrNi entropy alloy and Q235B steel, the problem of difficulty in bonding the materials during the composite process is solved, and composite sheets with high strength and high bonding rates are achieved.

CN119501270AActive Publication Date: 2025-02-25GANSU FANGHENG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411783556.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-25
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The prior art has failed to effectively solve the explosive composite problem of CoCrNi entropy alloy and Q235B steel, which has resulted in difficulty in bonding the materials during the composite process and strength loss.

Method used

Cast steel anvil is used as the backing plate, Q235B steel is used as the substrate, CoCrNi medium entropy alloy is used as the compound plate, and kraft cardboard is used as the partition between explosives and compound plates. Homemade high-vibration explosives are used for explosion welding to control the explosion speed and intensity of the explosives. Achieve metallurgical connection.

Benefits of technology

The efficient metallurgical connection between CoCrNi medium-entropy alloy and Q235B steel is achieved, which improves the strength and bonding rate of the composite plate, and makes up for the material strength loss caused by complete annealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501270A_ABST
    Figure CN119501270A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a CoCrNi medium-entropy alloy and Q235B steel explosive welding composite board, which comprises the following steps of: annealing a CoCrNi medium-entropy alloy board, sequentially laying sandy soil, an anvil, a Q235B hot-rolled steel plate, a support column, a medium-entropy alloy board, kraft paper and explosive from bottom to top on an explosion field, and performing explosive welding to obtain the CoCrNi medium-entropy alloy and Q235B steel explosive welding composite board. The detonation velocity of the explosive ranges from 2500 m / s to 3000 m / s, and the brisance of the explosive ranges from 18 mm to 22 mm. According to the method, metallurgical bonding of the CoCrNi medium entropy alloy and the Q235B steel plate is achieved, the interface bonding rate of the obtained composite plate is larger than 99.2%, the yield strength is larger than 420 MPa, the tensile strength is larger than 500 MPa, the percentage elongation after fracture is larger than 35%, and the interface shear strength is larger than 200 MPa. The method is simple in process and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of metal-based composite materials, and specifically provides a method for preparing a composite plate of CoCrNi medium-entropy alloy and Q235B steel explosively welded, belonging to the field of metal composite material processing. Background Art

[0002] The CoCrNi medium entropy alloy with equal atomic ratio is a new type of structural material developed in recent years. It has high strength, high toughness, excellent comprehensive properties such as friction and wear resistance, corrosion resistance, radiation resistance, and high temperature resistance. It has significant application potential in transportation, aerospace and other fields. However, due to the high Co content in the alloy, its cost is also high. Q235B steel is one of the most widely used steels due to its extremely low manufacturing cost, but Q235B steel has low mechanical properties and corrosion resistance, which means it can only be used in fields that do not require high material properties.

[0003] Dissimilar metal layered composites have attracted widespread attention due to their combination of the advantages of various metal materials, and their scope of use has been continuously expanded. The composite of CoCrNi medium entropy alloy and Q235B can not only significantly reduce the cost, but also keep the overall mechanical properties and corrosion resistance of the material high. For layered metal composite plates, the most commonly used composite methods are solid-liquid composite, rolling composite and explosive composite. However, the melting point difference between CoCrNi medium entropy alloy and Q235B steel is not large, and they are not suitable for solid-liquid composite. The significant differences between the two materials in mechanical properties, work hardening ability and antioxidant ability also determine that they are not suitable for rolling composite. As an important means of preparing dissimilar metal layered composites, the explosive welding method can theoretically realize the composite of all metal materials, but its explosion process is greatly affected by multiple factors and the parameters of each factor. At present, there is no relevant technical report on the explosive composite of CoCrNi medium entropy alloy and Q235B steel.

[0004] Therefore, developing a technology for explosive welding of CoCrNi medium entropy alloy and Q235B steel is a key issue that needs to be urgently solved in the field of composite plate manufacturing technology. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a method for preparing a composite plate of CoCrNi medium entropy alloy and Q235B steel explosive welding. The preparation method provided by the present invention uses a cast steel anvil as a backing plate, Q235B steel as a substrate, a CoCrNi medium entropy alloy as a composite plate, and kraft paper as an interlayer between explosives and the composite plate during the explosive welding process, and adopts self-made high-intensity explosives to achieve metallurgical connection of the plates. The process of the present invention is simple and convenient, and is suitable for industrial production.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The invention discloses a preparation method of a CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate. The method comprises the following steps: annealing the CoCrNi medium entropy alloy plate, laying sand, anvil, Q235B hot-rolled steel plate, support column, medium entropy alloy plate, kraft paper and explosives in sequence from bottom to top on an explosion field, and then performing explosion welding to obtain the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate. The explosive has a detonation velocity of 2500-3000 m / s and a ferocity of 18-22 mm.

[0008] The preparation method of the present invention firstly performs a complete annealing treatment on the CoCrNi medium entropy alloy to improve the plasticity of the alloy, and Q235B steel is selected as a hot-rolled steel plate with good plasticity and medium strength. Based on the above properties of the two, it can be ensured that they are easy to combine in the explosion process without cracking, and then the Q235B steel is used as a substrate, the CoCrNi medium entropy alloy is used as a composite plate, and the kraft paper board is used as an interlayer between the explosive and the composite plate. Finally, the explosive provided by the present invention is used for explosion welding to obtain a composite material with metallurgical bonding, wherein the detonation speed is controlled within the scope of the present invention, so that the composite interface of the two plates in the present invention can be a small wave bonding interface, and the bonding strength is improved, and the high fierceness of the explosive can cause the substrate and the composite plate to undergo severe work hardening during the explosion process, thereby improving the strength of the material and compensating for the material strength loss caused by the complete annealing of the CoCrNi medium entropy alloy before the explosion composite. The preparation method of the present invention fully utilizes the characteristics of the soft CoCrNi medium entropy alloy having excellent work hardening ability, and ensures that the final composite plate can achieve a higher strength without heat treatment.

[0009] As a preferred embodiment, the length × width × thickness of the Q235B hot-rolled steel plate is: (500~800) mm × (400~600) mm × (10~40) mm, the length × width × thickness of the CoCrNi medium-entropy alloy plate is: (510~810) mm × (410~610) mm × (2~5) mm, and the length and width of the CoCrNi medium-entropy alloy plate are both greater than the length and width of the Q235B hot-rolled steel plate.

[0010] In the present invention, the high-cost medium-entropy alloy plate is selected as a thin plate, and the low-cost Q235B hot-rolled steel plate is used as a thick plate. In the process of explosive composite, the Q235B hot-rolled steel plate is used as the base plate and the medium-entropy alloy plate is used as the composite plate, which has better support.

[0011] As a preferred solution, the surface roughness Ra of the CoCrNi medium entropy alloy plate and the Q235B hot-rolled steel plate is ≤3 μm. In actual operation, the surface of the substrate and the composite plate is polished before use to remove surface oil and oxides to ensure that the surface roughness Ra is ≤3 μm.

[0012] As a preferred solution, the CoCrNi medium entropy alloy plate is annealed at a temperature of 1000-1100° C. and for a time of 1-2 h.

[0013] By completely softening and annealing the medium entropy alloy plate within the above parameters, the alloy has good plasticity, ensuring that the explosion process can easily achieve metallurgical bonding of the material without cracking.

[0014] In the present invention, commercially available Q235B hot-rolled steel plates are used, which have good plasticity and medium strength and do not require heat treatment.

[0015] In industrial applications, a flat hard soil site is selected as the blasting site, and a layer of sand is laid on the hard soil as the foundation;

[0016] As a preferred solution, the thickness of the sand is 20-25 mm.

[0017] As a preferred solution, the anvil is made of cast steel and has a thickness of 50-55 mm.

[0018] In the present invention, due to the use of high-strength explosives, the explosion process not only has a greater impact force on the base plate and the composite plate, but also has a greater impact on the anvil plate. Based on the properties of Q235B hot-rolled steel plate, a cast steel anvil plate with good rigidity is placed under the soft base plate in industrial production to avoid serious bending and deformation of the composite plate during the explosion process.

[0019] During the actual operation, the anvil should be parallel to the ground and must not be tilted. The upper surface of the anvil should be cleaned and kept smooth, and the Q235B hot-rolled steel plate should be placed in the center area of ​​the anvil.

[0020] Preferably, the length and width of the anvil are both 1000-3000 mm. The anvil should be parallel to the ground and should not be tilted, and the upper surface of the anvil should be cleaned.

[0021] As a preferred solution, support columns are arranged at the four corners of the surface of the Q235B hot-rolled steel plate, and the CoCrNi medium-entropy alloy plate is placed above the support columns to ensure that the center position of the CoCrNi medium-entropy alloy plate and the center position of the Q235B hot-rolled steel plate are on the same axis, and the four sides are parallel to the four sides of the Q235B hot-rolled steel plate.

[0022] Further preferably, the support column has a diameter of 10-12 mm and a height of 6-8 mm.

[0023] As a preferred solution, the CoCrNi medium entropy alloy plate is surrounded by wooden strips on all sides, and the upper surface of the wooden strips is controlled to be higher than the surface of the CoCrNi medium entropy alloy plate to serve as an explosive pool, and the depth of the explosive pool is 50-70 mm.

[0024] During industrial applications, kraft paper is placed in the explosive pool to isolate the explosive from direct contact with the composite plate, and to act as a buffer and protect the plate surface during explosion. Then, the explosive pool on the kraft paper is evenly filled with a low-detonation-velocity and high-intensity mixed explosive, ensuring that the thickness of the explosive is uniform during the filling process.

[0025] As a preferred embodiment, the explosive has the following composition by mass fraction: 55-65% antimony-free rock ammonium nitrate explosive, 5-15% calcium carbonate powder, 5-10% sodium chloride, 5-10% silicon carbide powder, 5-10% perlite powder, 5-10% wood chips, and 5-10% chromium powder.

[0026] The explosive components of the present invention use antimony-free rock ammonium nitrate as the basic explosive. Calcium carbonate, sodium chloride and silicon carbide powder are added to the basic explosive to reduce the detonation velocity of the explosive. The addition of perlite powder and crushed wood chips can improve the fluffiness of the explosive, which is conducive to detonation. The addition of chromium powder can improve the explosive strength. Through the synergy of the above explosive components, an explosive with a detonation velocity of 2500-3000 m / s and a strength of 18-22 mm is obtained. The use of the explosive of the present invention can not only obtain a detonation velocity adapted to a plate, but also control the amplitude of a composite interface waveform, form a small wave bonding interface, and improve bonding strength. The high-strength explosive can cause a base plate and a composite plate to undergo severe work hardening during the explosion process, thereby compensating for the material strength loss caused by complete annealing before the explosion composite.

[0027] In industrial applications, the explosives must be prepared, dried, and mixed evenly within 1 hour before use, and then sieved through a 40-mesh sieve to select a -40-mesh mixed powder as the explosive to be used. When using, water must be added to the mixed explosives, and the volume percentage of water in the mixed explosives must be controlled to 5%, and mixed evenly before laying.

[0028] As a preferred embodiment, the mesh size of the explosive is -40 mesh, and the density of the explosive is 0.8-0.9 g / cm 3 .

[0029] As a preferred solution, a detonator is installed in the explosive, and the detonator is installed at the center of the short side direction of the Q235B steel plate and the CoCrNi medium entropy alloy plate, and then a lead is connected to the detonator, and finally the connecting lead is connected to the remote control detonation device, and the detonator is detonated by the detonator through the connecting lead to complete the explosive welding, that is, the CoCrNi medium entropy alloy and Q235B steel explosive welded composite plate. The inventor found that arranging the detonator to the short side can improve the yield.

[0030] In a further preferred embodiment, three quarters of the detonator is buried in the explosive.

[0031] In industrial production, the board surface after explosive compounding needs to be cleaned and leveled, and the cracked and collapsed parts of the edges need to be cut off. Finally, ultrasonic flaw detection is used to ensure that the entire board surface is well bonded.

[0032] The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate prepared by the present invention is greater than 99.2%, the yield strength is greater than 420 MPa, the tensile strength is greater than 500 MPa, the elongation after fracture is greater than 35%, and the interface shear strength is greater than 200 MPa.

[0033] Principles and advantages

[0034] The present invention realizes metallurgical connection between CoCrNi medium entropy alloy and Q235B steel through explosive welding, and provides a preparation method of high-performance bimetallic composite plate suitable for industrial production. During explosive welding production, the selection of various parameters of explosive welding has a crucial influence on the performance of the final composite plate. After multiple experiments, the present invention explores suitable process parameters for explosive welding of CoCrNi medium entropy alloy and Q235B steel.

[0035] Before explosive welding, the selected CoCrNi medium entropy alloy is completely annealed to improve the plasticity of the alloy; Q235B steel uses hot-rolled steel plates, which have good plasticity and medium strength. Based on the performance characteristics of these two materials, it is guaranteed that the explosion process is easy to combine without cracking. In industrial production, a cast steel anvil with good rigidity is placed under the soft substrate to avoid serious bending and deformation of the composite plate during the explosion process. By controlling the detonation velocity of the explosive, the composite interface is combined in a small wave; the use of high-strength explosives can cause the substrate and the composite plate to undergo severe work hardening during the explosion, improve the strength of the material, and make up for the material strength loss caused by the complete annealing of the CoCrNi medium entropy alloy before the explosive composite. This technology makes full use of the excellent work hardening ability of the soft CoCrNi medium entropy alloy, ensuring that the final composite plate can achieve a high strength without heat treatment.

[0036] The present invention obtains a composite plate of CoCrNi medium entropy alloy and Q235B steel by explosive welding for the first time. The interface bonding rate of the composite plate is greater than 99.2%, the yield strength is greater than 420MPa, the tensile strength is greater than 500MPa, the elongation after fracture is greater than 35%, and the interface shear strength is greater than 200MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Process structure of explosive welding of CoCrNi medium entropy alloy and Q235B steel;

[0038] Figure 2 Explosion welding samples of the CoCrNi medium entropy alloy and Q235B steel obtained in Example 1;

[0039] Figure 3 The interface morphology of the explosively welded composite plate of CoCrNi medium entropy alloy and Q235B steel obtained in Example 1 shows a small wavy bonding interface. DETAILED DESCRIPTION

[0040] The following are preferred embodiments of the present invention, but not all embodiments. Without departing from the principle of the process innovation, any equivalent process transformation made by using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, shall be deemed as the patent protection scope of the present invention.

[0041] Example 1

[0042] The CoCrNi medium entropy alloy plate and the commercially available hot-rolled Q235B steel plate which were completely softened and annealed at 1000℃ / 2h were selected as raw materials, and the following steps were followed:

[0043] S1. Cut out Q235B steel plates with a length × width of 500 mm × 400 mm and a thickness of 10 mm and CoCrNi medium-entropy alloy plates with a length × width of 510 mm × 410 mm and a thickness of 2 mm respectively; use a sanding belt to grind one side of the two alloy plates to remove surface oil and oxides to ensure that their surface roughness Ra ≤ 3 μm.

[0044] S2. Select a flat hard soil site as the blasting site, and lay a 20mm layer of sand on the hard soil as the foundation.

[0045] S3. Place a cast steel anvil with dimensions of 1000mm×1500mm×50mm parallel to the ground on the foundation and clean its surface.

[0046] S4. Place a 10 mm thick Q235B steel plate with the polished surface facing upwards in the center area of ​​the cast steel anvil.

[0047] S5. Four aluminum alloy columnar support columns with a diameter of 12 mm and a height of 6 mm are arranged at the four corners of the surface of the Q235B steel plate.

[0048] S6. Place a 2 mm thick CoCrNi medium entropy alloy plate with the polished surface facing downward on the support column; and ensure that the center position of the medium entropy alloy and the center position of the Q235B steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.

[0049] S7. Surround the medium-entropy alloy with wooden strips, with the upper surface of the wooden strips 50 mm higher than the surface of the medium-entropy alloy, as an explosive pool.

[0050] S8. Lay a layer of kraft paper at the bottom of the explosive pool to prevent direct contact between the explosives and the composite plate.

[0051] S9. Evenly spread the homemade high-strength mixed explosive in the explosive pool above the kraft paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is: 55% antimony-free rock ammonium nitrate explosive, 10% calcium carbonate powder, 10% sodium chloride, 5% silicon carbide powder, 5% perlite powder, 10% wood chips, and 5% chromium powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved through a 40-mesh sieve, and a -40-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 2500m / s, the strength is 18mm, and the density is: 0.8g / cm 3 .

[0052] S10. The detonator is detonated by connecting the wire and the detonator to obtain a composite plate of CoCrNi medium entropy alloy and Q235B steel.

[0053] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.

[0054] The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate prepared by the present process is 99.5%, the yield strength is 438 MPa, the tensile strength is 515 MPa, the elongation after fracture is 36.7%, and the interface shear strength is 212 MPa.

[0055] Example 2

[0056] The CoCrNi medium entropy alloy plate and the commercially available hot-rolled Q235B steel plate which were completely softened and annealed at 1000℃ / 2h were selected as raw materials, and the following steps were followed:

[0057] S1. Cut out Q235B steel plates with a length × width of 600 mm × 500 mm and a thickness of 30 mm and CoCrNi medium-entropy alloy plates with a length × width of 610 mm × 510 mm and a thickness of 3 mm respectively; use a sanding belt to grind one side of the two alloy plates to remove surface oil and oxides to ensure that their surface roughness Ra ≤ 3 μm.

[0058] S2. Select a flat hard soil site as the blasting site and lay a 20mm layer of sand on the hard soil as the foundation.

[0059] S3. Place a cast steel anvil with dimensions of 1000mm×1500mm×50mm parallel to the ground on the foundation and clean its surface.

[0060] S4. Place a 30 mm thick Q235B steel plate with the polished surface facing upwards in the center area of ​​the cast steel anvil.

[0061] S5. Four aluminum alloy columnar support columns with a diameter of 12 mm and a height of 6 mm are arranged at the four corners of the surface of the Q235B steel plate.

[0062] S6. Place a 3 mm thick CoCrNi medium entropy alloy plate with the polished surface facing downward on the support column; and ensure that the center position of the medium entropy alloy and the center position of the Q235B steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.

[0063] S7. Use wooden strips to surround the medium entropy alloy, with the upper surface of the wooden strips 60mm higher than the surface of the medium entropy alloy, as an explosive pool.

[0064] S8. Lay a layer of kraft paper at the bottom of the explosive pool to prevent direct contact between the explosives and the composite plate.

[0065] S9. Evenly spread the homemade high-strength mixed explosive in the explosive pool above the kraft paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is: 60% antimony-free rock ammonium nitrate explosive, 15% calcium carbonate powder, 5% sodium chloride, 5% silicon carbide powder, 5% perlite powder, 5% wood chips, and 5% chromium powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved through a 40-mesh sieve, and a -40-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 2700m / s, the strength is 18mm, and the density is: 0.83g / cm 3 .

[0066] S10. The detonator is detonated by connecting the wire and the detonator to obtain a composite plate of CoCrNi medium entropy alloy and Q235B steel.

[0067] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.

[0068] The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate prepared by the present process is 99.6%, the yield strength is 435 MPa, the tensile strength is 512 MPa, the elongation after fracture is 37.1%, and the interface shear strength is 213 MPa.

[0069] Example 3

[0070] The CoCrNi medium entropy alloy plate and the commercially available hot-rolled Q235B steel plate which were completely softened and annealed at 1000℃ / 2h were selected as raw materials, and the following steps were followed:

[0071] S1. Cut out Q235B steel plates with a length × width of 800 mm × 600 mm and a thickness of 40 mm and CoCrNi medium-entropy alloy plates with a length × width of 810 mm × 610 mm and a thickness of 5 mm respectively; use a sanding belt to grind one side of the two alloy plates to remove surface oil and oxides to ensure that their surface roughness Ra ≤ 3 μm.

[0072] S2. Select a flat hard soil site as the blasting site and lay a 20mm layer of sand on the hard soil as the foundation.

[0073] S3. Place a cast steel anvil with dimensions of 1000mm×1500mm×50mm parallel to the ground on the foundation and clean its surface.

[0074] S4. Place a 40 mm thick Q235B steel plate with the polished surface facing upwards in the center area of ​​the cast steel anvil.

[0075] S5. Four aluminum alloy columnar support columns with a diameter of 12 mm and a height of 6 mm are arranged at the four corners of the surface of the Q235B steel plate.

[0076] S6. Place a 5 mm thick CoCrNi medium entropy alloy plate with the polished surface facing downward on the support column; and ensure that the center position of the medium entropy alloy and the center position of the Q235B steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.

[0077] S7. Use wooden strips to surround the medium entropy alloy, with the upper surface of the wooden strips 70mm higher than the surface of the medium entropy alloy, as an explosive pool.

[0078] S8. Lay a layer of kraft paper at the bottom of the explosive pool to prevent direct contact between the explosives and the composite plate.

[0079] S9. Evenly spread the homemade high-strength mixed explosive in the explosive pool above the kraft paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is: 60% antimony-free rock ammonium nitrate explosive, 10% calcium carbonate powder, 5% sodium chloride, 5% silicon carbide powder, 5% perlite powder, 5% wood chips, and 10% chromium powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved through a 40-mesh sieve, and a -40-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 3000m / s, the strength is 22mm, and the density is: 0.9g / cm 3 .

[0080] S10. The detonator is detonated by connecting the wire and the detonator to obtain a composite plate of CoCrNi medium entropy alloy and Q235B steel.

[0081] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.

[0082] The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate prepared by the present process is 99.2%, the yield strength is 421 MPa, the tensile strength is 503 MPa, the elongation after fracture is 35.2%, and the interface shear strength is 202 MPa.

[0083] Example 4

[0084] The CoCrNi medium entropy alloy plate and the commercially available hot-rolled Q235B steel plate which were completely softened and annealed at 1000℃ / 2h were selected as raw materials, and the following steps were followed:

[0085] S1. Cut out Q235B steel plates with a length × width of 700 mm × 500 mm and a thickness of 20 mm and CoCrNi medium-entropy alloy plates with a length × width of 710 mm × 510 mm and a thickness of 4 mm respectively; use a sanding belt to grind one side of the two alloy plates to remove surface oil and oxides to ensure that their surface roughness Ra ≤ 3 μm.

[0086] S2. Select a flat hard soil site as the blasting site and lay a 20mm layer of sand on the hard soil as the foundation.

[0087] S3. Place a cast steel anvil with dimensions of 1000mm×1500mm×50mm parallel to the ground on the foundation and clean its surface.

[0088] S4. Place a 20 mm thick Q235B steel plate with the polished surface facing upwards in the center area of ​​the cast steel anvil.

[0089] S5. Four aluminum alloy columnar support columns with a diameter of 12 mm and a height of 6 mm are arranged at the four corners of the surface of the Q235B steel plate.

[0090] S6. Place a 4 mm thick CoCrNi medium entropy alloy plate with the polished surface facing downward on the support column; and ensure that the center position of the medium entropy alloy and the center position of the Q235B steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.

[0091] S7. Use wooden strips to surround the medium entropy alloy, with the upper surface of the wooden strips 65mm higher than the surface of the medium entropy alloy, as an explosive pool.

[0092] S8. Lay a layer of kraft paper at the bottom of the explosive pool to prevent direct contact between the explosives and the composite plate.

[0093] S9. Evenly spread the homemade high-strength mixed explosive in the explosive pool above the kraft paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is: 65% antimony-free rock ammonium nitrate explosive, 10% calcium carbonate powder, 5% sodium chloride, 5% silicon carbide powder, 5% perlite powder, 5% wood chips, and 5% chromium powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved through a 40-mesh sieve, and a -40-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 2700m / s, the strength is 18mm, and the density is: 0.82g / cm 3 .

[0094] S10. The detonator is detonated by connecting the wire and the detonator to obtain a composite plate of CoCrNi medium entropy alloy and Q235B steel.

[0095] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.

[0096] The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate prepared by the present process is 99.5%, the yield strength is 423 MPa, the tensile strength is 508 MPa, the elongation after fracture is 35.9%, and the interface shear strength is 210 MPa.

[0097] Example 5

[0098] The CoCrNi medium entropy alloy plate and the commercially available hot-rolled Q235B steel plate which were completely softened and annealed at 1000℃ / 2h were selected as raw materials, and the following steps were followed:

[0099] S1. Cut out Q235B steel plates with a length × width of 800 mm × 400 mm and a thickness of 35 mm and CoCrNi medium-entropy alloy plates with a length × width of 810 mm × 410 mm and a thickness of 2.5 mm respectively; use a sanding belt to grind one side of the two alloy plates to remove surface oil and oxides to ensure that their surface roughness Ra ≤ 3 μm.

[0100] S2. Select a flat hard soil site as the blasting site and lay a 20mm layer of sand on the hard soil as the foundation.

[0101] S3. Place a cast steel anvil with dimensions of 1000mm×1500mm×50mm parallel to the ground on the foundation and clean its surface.

[0102] S4. Place a 35 mm thick Q235B steel plate with the polished surface facing upwards in the center area of ​​the cast steel anvil.

[0103] S5. Four aluminum alloy columnar support columns with a diameter of 12 mm and a height of 6 mm are arranged at the four corners of the surface of the Q235B steel plate.

[0104] S6. Place a 2.5 mm thick CoCrNi medium entropy alloy plate with the polished surface facing downward on the support column; and ensure that the center position of the medium entropy alloy and the center position of the Q235B steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.

[0105] S7. Use wooden strips to surround the medium entropy alloy, with the upper surface of the wooden strips 60mm higher than the surface of the medium entropy alloy, as an explosive pool.

[0106] S8. Lay a layer of kraft paper at the bottom of the explosive pool to prevent direct contact between the explosives and the composite plate.

[0107] S9. Evenly spread the homemade high-strength mixed explosive in the explosive pool above the kraft paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is: 58% antimony-free rock ammonium nitrate explosive, 5% calcium carbonate powder, 5% sodium chloride, 10% silicon carbide powder, 10% perlite powder, 5% wood chips, and 7% chromium powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved through a 40-mesh sieve, and a -40-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 2800m / s, the strength is 20mm, and the density is: 0.88g / cm 3 .

[0108] S10. The detonator is detonated by connecting the wire and the detonator to obtain a composite plate of CoCrNi medium entropy alloy and Q235B steel.

[0109] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.

[0110] The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate prepared by the present process is 99.3%, the yield strength is 430 MPa, the tensile strength is 512 MPa, the elongation after fracture is 36.2%, and the interface shear strength is 215 MPa.

[0111] Comparative Example 1

[0112] The other conditions are the same as those in Example 1, except that the CoCrNi medium-entropy alloy is not annealed before the explosive composite, that is, the composite plate material is a hard CoCrNi medium-entropy alloy. Since the hard medium-entropy alloy has high strength and poor plasticity, it cannot withstand strong plastic deformation during the explosive composite process. Therefore, after the explosion, the medium-entropy alloy composite plate is cracked due to the strong impact force generated by the explosives, and the composite fails.

[0113] Comparative Example 2

[0114] The other conditions are the same as those in Example 1, except that a sieve of 80 mesh is used for screening the mixed explosive. Since calcium carbonate and sodium chloride in the explosive components are easy to agglomerate, when a sieve finer than 40 mesh is used for screening, more agglomerated calcium carbonate and sodium chloride in the mixed explosive are screened out, resulting in a decrease in the content of calcium carbonate and sodium chloride in the explosive components after screening. The reduction in the content of these two components will cause the detonation velocity of the explosive to increase. Therefore, after screening with a sieve of 80 mesh, the detonation velocity of the explosive is 3250 m / s, which exceeds the suitable detonation velocity range of the explosive shown in the present invention. The interface after explosive composite is in a large wavy shape, and the content of the molten zone is much higher than that in Example 1. The yield strength of the composite plate is only 400 MPa, the tensile strength is only 480 MPa, and the interface shear strength is only 165 MPa. The performance of the composite plate is lower than that of Example 1.

[0115] Comparative Example 3

[0116] The other conditions are the same as those in Example 1, except that the explosive composition is changed to: 70% antimony-free rock ammonium nitrate explosive, 10% sodium chloride, 5% silicon carbide powder, 5% perlite powder, and 10% wood chips. The calcium carbonate that reduces the detonation velocity and the chromium powder that increases the intensity are removed from the explosive composition. Under this composition ratio, the detonation velocity of the explosive is 3200m / s and the intensity is 13mm. The increase in the detonation velocity leads to the formation of a large wave interface and a large-scale melting zone; the decrease in intensity reduces the force provided by the explosion process, resulting in a decrease in the interface bonding rate. When the explosive composition is used for explosive compounding, the interface bonding rate is only 28%.

Claims

1. A method for preparing a composite plate of CoCrNi medium entropy alloy and Q235B steel by explosive welding, characterized in that: The CoCrNi medium entropy alloy plate is annealed, and then sand, anvil, Q235B hot-rolled steel plate, support column, medium entropy alloy plate, kraft paper and explosives are laid in sequence from bottom to top on the explosion field, and then explosive welding is performed to obtain the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate, wherein the detonation velocity of the explosive is 2500-3000 m / s and the intensity is 18-22 mm.

2. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1, characterized in that: The length×width×thickness of the Q235B hot-rolled steel plate is: 500~800mm×400~600mm×10~40mm, the length×width×thickness of the CoCrNi medium entropy alloy plate is: 510~810mm×410~610mm×2~5mm, and the length and width of the CoCrNi medium entropy alloy plate are greater than the length and width of the Q235B hot-rolled steel plate; The surface roughness Ra of the CoCrNi medium entropy alloy plate and the Q235B hot-rolled steel plate are both ≤3 μm.

3. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The CoCrNi medium entropy alloy plate is annealed at a temperature of 1000-1100° C. and for a time of 1-2 h.

4. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The thickness of the sand is 20-25 mm; The material of the anvil is cast steel, and the thickness of the anvil is 50-55 mm; The length and width of the anvil are both 1000-3000 mm.

5. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The support columns are arranged at the four corners of the surface of the Q235B hot-rolled steel plate, and the CoCrNi medium entropy alloy plate is placed above the support columns to ensure that the center position of the CoCrNi medium entropy alloy plate and the center position of the Q235B hot-rolled steel plate are on the same axis, and the four sides of the CoCrNi medium entropy alloy plate are parallel to the four sides of the Q235B hot-rolled steel plate; The support column has a diameter of 10-12 mm and a height of 6-8 mm.

6. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The CoCrNi medium entropy alloy plate is surrounded by wooden strips on all sides, and the upper surface of the wooden strips is controlled to be higher than the surface of the CoCrNi medium entropy alloy plate to serve as an explosive pool, and the depth of the explosive pool is 50-70 mm.

7. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The explosive has the following components by mass percentage: 55-65% antimony-free rock ammonium nitrate explosive, 5-15% calcium carbonate powder, 5-10% sodium chloride, 5-10% silicon carbide powder, 5-10% perlite powder, 5-10% wood chips, and 5-10% chromium powder.

8. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The mesh number of the explosive is -40 mesh, and the density of the explosive is 0.8-0.9 g / cm 3 .

9. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: A detonator is installed in the explosive, the detonator is installed at the center position of the short side direction of the Q235B steel plate and the CoCrNi medium entropy alloy plate, and then a lead is connected to the detonator, and finally the connecting lead is connected to a remote control detonating device, and the detonator is detonated by a detonator through the connecting lead to complete the explosive welding, so as to obtain a CoCrNi medium entropy alloy and Q235B steel explosive welded composite plate; three quarters of the detonator is buried in the explosive.

10. The method for preparing a CoCrNi medium entropy alloy and Q235B steel explosively welded composite plate according to claim 1 or 2, characterized in that: The interface bonding rate of the CoCrNi medium entropy alloy and Q235B steel explosion-welded composite plate is greater than 99.2%, the yield strength is greater than 420 MPa, the tensile strength is greater than 500 MPa, the elongation after fracture is greater than 35%, and the interface shear strength is greater than 200 MPa.

Citation Information

Patent Citations

  • W6Mo5Cr4V2 / Q345 explosive welding composite material

    CN103009702A

  • Manufacturing method of multi-element high-entropy alloy dispersion copper rod layered composite material

    CN113414486A

  • Preparation method of aluminum-magnesium alloy and magnesium-aluminum-zinc alloy explosive welding composite board

    CN115007991A

  • Equipment high-toughness Al0. 3CoCrFeNi / 304L composite board and manufacturing method thereof

    CN116475551A

  • Production method for explosive welding super-long chromium molybdenum vanadium hydroforming steel 12Cr2Mo1VR metal composite plate

    CN116871654A

Cited By

  • Explosive welding method for composite spherical crown lining plate

    CN119681405A

  • Large-size tin-phosphor bronze / Q235B composite board and preparation method thereof

    CN121649545A

  • 4J29 kovar alloy / 304 stainless steel composite board and preparation method thereof

    CN121649700A